Comparative Analysis of Secure and Energy Efficient routing protocols in Wireless sensor network (International Journal of Engineering and Computer Science, 2014)
Hierarchical routing architecture divides the whole network into a group of cluster and only cluster head is responsible to forwarding the data to base station directly. In hierarchical based architecture of routing, the cluster head is used to aggregate the data from other nodes and send the aggregated data to Base station.During the creation of network topology, the process of setting up routes in WSNs is usually influenced by energy considerations, because the power consumption of a wireless link is proportional to square or even higher order of the distance between the sender and the receiver. In hierarchical routing architecture, sensor nodes self-configure themselves for the formation of cluster heads. In this paper, the survey on energy efficient and secure routing protocol in wireless sensor network and few of them are compared and evaluated.